2014
DOI: 10.1038/ejcn.2014.224
|View full text |Cite
|
Sign up to set email alerts
|

The Danish tax on saturated fat: why it did not survive

Abstract: The analysis indicates that the Danish tax on fat was introduced mainly to increase public revenue. As the tax had no strong proponents and many influential adversaries, it was repealed. New research indicates that the tax was effective in changing consumer behaviour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
46
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(47 citation statements)
references
References 6 publications
1
46
0
Order By: Relevance
“…Although not specifically aimed at meat consumption (and motivated more by economics than health), Denmark operated a tax on the saturated fat content of foods between 2011 and 2012 that raised prices of some meat products by 15% (82). Since its repeal, analyses of panel data have shown that the tax accompanied reductions in consumption of products high in saturated fat, including minced beef (83), and modeling of long-term health outcomes suggests a reduction in noncommunicable disease and premature mortality (84).…”
Section: Changing Dietsmentioning
confidence: 99%
“…Although not specifically aimed at meat consumption (and motivated more by economics than health), Denmark operated a tax on the saturated fat content of foods between 2011 and 2012 that raised prices of some meat products by 15% (82). Since its repeal, analyses of panel data have shown that the tax accompanied reductions in consumption of products high in saturated fat, including minced beef (83), and modeling of long-term health outcomes suggests a reduction in noncommunicable disease and premature mortality (84).…”
Section: Changing Dietsmentioning
confidence: 99%
“…Currently, strategies to combat the rise of diet-related disease in the developed world focus on manipulating the food environment to increase purchasing of 'healthy' foods and decrease purchasing of 'unhealthy' foods. Examples of interventions include food labelling (5) , food taxes (6) , advertising restrictions (7) and food reformulation (8) .…”
mentioning
confidence: 99%
“…85 Hence, the description of Behavioural Economics as psychologism is not pejorative; rather, it should be taken as a compliment with internal validity derived from the methods of 82 Madden (2015), 106; see also Vallgarda et al (2015).…”
mentioning
confidence: 99%